Influence of whistle blowing on unethical behaviour in Jabatan Kastam Diraja Malaysia (JKDM) / Azman Rafie Abdul Rahman, Mohd Adha Ibrahim and Nurul Nazlia Jamil - Abdul Rahman, Azman Rafie; Ibrahim, Mohd Adha; Jamil, Nurul Nazlia (UiTM Cawangan Johor, 2019)
This paper is to investigate the relationship between whistle-blowing practice and unethical behavior at the Royal Malaysian Customs Department in Putrajaya which represent the Royal Customs Department’s organizations in general. The study was also conducted to determine whether whistle-blowing practice would influence the efforts to reduce unethical behavior among Jabatan Kastam Diraja Malaysia (JKDM) officers and members. Other than that, this study was also identified the level of unethical behavior and the whistle blowing practice of the organizations among the officers and members of the JKDM Putrajaya. A total of 300 questionnaire were distributed, only 182 questionnaires were quoted for the analysis. Data were analysed using the SPSS software. The findings show that, the level of unethical behaviour among officers and members of JKDM is low. The whistle-blowing practice is at a high level in accordance with the perception of officers and members of JKDM Putrajaya. Whistle-blowing policies that have been studied, have insignificant value with the unethical behaviour compare to the whistle blowing practices, that have a significant value and the value is moderate. In the multiple regression analysis showed, only the whistle-blowing practice has a significant value on the ethical behavior. Hence, the management, policy maker and JKDM leaders should pay attention to the seriousness of the distribution mechanism or whistle-blowing as one of the efforts to combat the unethical behavior among officers and JKDM members.